Appendicitis in the Geriatric Population: A Literature Review - Inamullah; Gutti, Tejeswi S; Khan, Mohammad Burhan; Asim, Affan; Ali, syed Muhammad (International Journal of Innovative Research in Medical Science, 2024)
Objective: This literature review examines the unique characteristics, challenges, and management strategies for appendicitis in the geriatric population, an age group often facing atypical symptom presentations and increased morbidity and mortality rates. Methods: A systematic review was conducted across multiple academic databases, including PubMed, Medline, and Google Scholar, to identify relevant articles on appendicitis in elderly patients, published upto June 2024. Keywords such as "appendicitis," "geriatric," "elderly," and "appendectomy" were used to retrieve studies examining the epidemiology, clinical presentation, diagnosis, treatment, and outcomes for elderly patients. Results: Elderly patients with appendicitis frequently present atypically, with symptoms that are often subtle or overlap with other age-related conditions, increasing diagnostic delays and complication rates. A higher incidence of perforation, longer hospital stays, and elevated rates of malignancy were noted in this population. Imaging, especially CT scans, emerged as a critical diagnostic tool due to the reduced sensitivity of traditional scoring systems in elderly patients. Treatment approaches, including surgical and conservative methods, highlight a need for individualized management given the higher risk of postoperative complications and frailty in geriatric patients. Conclusion: Appendicitis in elderly patients presents diagnostic and therapeutic challenges distinct from younger populations. Timely diagnosis, the use of advanced imaging, and judicious treatment selection are crucial to improving outcomes in this demographic. Further research is needed to refine diagnostic scoring systems and optimize treatment protocols specific to elderly patients with appendicitis.